2008
DOI: 10.1902/jop.2008.070205
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Multidrug‐Resistant Opportunistic Bacteria on the Gingiva During Leukemia Treatment

Abstract: The gingiva in patients undergoing leukemia treatment acts as sites of proliferation and reservoirs for multidrug-resistant opportunistic bacteria. Severe systemic infection by multidrug-resistant bacteria in such patients with leukemia also may involve the gingiva. To prevent abnormal increases in such bacteria on the gingiva, scaling and/or root planing before chemotherapy, which reduces bleeding on brushing during the neutropenic period caused by chemotherapy, may contribute to infection control in such pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Our previous studies showed that not only that normal oral flora but also opportunistic bacteria appear on the oral mucosa [7]. It was also reported that the appearance of multidrug-resistant opportunistic bacteria may be involved in fatal sepsis [4]. The reduced-intensity conditioning regimen for HCT leads to a reduction in the degree of oral mucositis, which may explain the reduced risk of infection in cases treated in this way.…”
Section: Discussionmentioning
confidence: 98%
“…Our previous studies showed that not only that normal oral flora but also opportunistic bacteria appear on the oral mucosa [7]. It was also reported that the appearance of multidrug-resistant opportunistic bacteria may be involved in fatal sepsis [4]. The reduced-intensity conditioning regimen for HCT leads to a reduction in the degree of oral mucositis, which may explain the reduced risk of infection in cases treated in this way.…”
Section: Discussionmentioning
confidence: 98%
“…Naime, zbog izostanka tipičnih simptoma gingivitisa (crvenilo, oteklina, bol) i slabijega imunosnog odgovora, parodontitis se kod tih bolesnika može lako previdjeti (18). Uz procjenu parodontološkog statusa, nužno je utvrditi stupanj oralne higijene već na početku bolesti kako bi se izbjegle neželjene komplikacije u kasnijim fazama kada počinje razvoj ozbiljnije neutropenije (19,20). Pokazalo se da pravodobno stomatološko zbrinjavanje onkoloških bolesnika smanjuje rizik od pojave oralnih komplikacija te pridonosi njihovoj kraćoj hospitalizaciji (21).…”
Section: Methodsunclassified
“…Periodontal disease can easily be overlooked, primarily because symptoms of gingival inflammation may be minimal with reduced erythema, swelling, and pain in sites of infection (18). A thorough assessment of the level of oral hygiene and of periodontal condition should be performed early in the workup for any patient in whom profound and prolonged neutropenia is anticipated in order to avoid later complications in these patients (19,20).…”
Section: Uvodmentioning
confidence: 99%
“…We also reported that multidrug-resistant opportunistic bacteria appearing in the gingiva may be involved in fatal sepsis [2]. These observations prompted an interest in the antibiotic sensitivity of bacteria after HCT, which may explain the bacterial substitution on oral mucosa after HCT.…”
mentioning
confidence: 91%